How to create a fair and equal absence management policy - Mortimore, Helen (Henry Stewart Talks, 2018)
This case study examines the difficulties being faced by a fictional photography company whose staff are complaining about they way their sickness absences are being handled, while some managers suspect that employees are taking sick leave as an entitlement, like vacation days. Questions are included in a written case study, and the speaker explains her own approach to overcoming these challenges.